The Cambridge Behavioural Inventory revised - Wear,Helen J. (2008)
Abstract Neurobehavioural and psychiatric symptoms are common in a range of neurodegenerative disorders with distinct profiles which are helpful in the diagnosis and monitoring of these disorders. The Cambridge Behavioural Inventory (CBI) has been shown to distinguish frontotemporal dementia (FTD), Alzheimer's disease (AD), Huntington's disease (HD) and Parkinson's disease (PD), but it is lengthy. Objective: To develop a shorter version of the 81 item CBI. Methods: CBI data from 450 participants with behavioural variant frontotemporal dementia (bv-FTD) (64), AD (96), PD (215) and HD (75) were analysed using Principal Components Analysis and measures of internal consistency (Cronbach alpha). Results: A reduced 45-item questionnaire was developed. The instrument identified distinct behavioural profiles and performed as well as the original version. Conclusions: A shorter (45 item) version of the CBI is capable of differentiating bv-FTD and AD from PD and HD. It may be useful in delineating the type and extent of problems in these disorders as well as monitoring therapeutic interventions.